Telomere Length, Traditional Risk Factors, Factors Related to Human Immunodeficiency Virus (HIV) and Coronary Artery Disease Events in Swiss Persons Living With HIV. (29th July 2020) - Engel, Tanja; Raffenberg, Marieke; Schoepf, Isabella C; Kootstra, Neeltje A; Reiss, Peter; Thorball, Christian W; Hasse, Barbara; Hirzel, Cédric; Wissel, Kerstin; Roth, Jan A; Bernasconi, Enos; Darling, Katharine E A; et al.
Abstract: Background: Leukocyte telomere length (TL) shortens with age and is associated with coronary artery disease (CAD) events in the general population. Persons living with human immunodeficiency virus (HIV; PLWH) may have accelerated atherosclerosis and shorter TL than the general population. It is unknown whether TL is associated with CAD in PLWH. Methods: We measured TL by quantitative polymerase chain reaction (PCR) in white Swiss HIV Cohort Study participants. Cases had a first CAD event during 1 January 2000 to 31 December 2017. We matched 1–3 PLWH controls without CAD events on sex, age, and observation time. We obtained univariable and multivariable odds ratios (OR) for CAD from conditional logistic regression analyses. Results: We included 333 cases (median age 54 years; 14% women; 83% with suppressed HIV RNA) and 745 controls. Median time (interquartile range) of TL measurement was 9.4 (5.9–13.8) years prior to CAD event. Compared to the 1st (shortest) TL quintile, participants in the 5th (longest) TL quintile had univariable and multivariable CAD event OR = 0.56 (95% confidence interval [CI], .35–.91) and OR = 0.54 (95% CI, .31–.96). Multivariable OR for current smoking was 1.93 (95% CI, 1.27–2.92), dyslipidemia OR = 1.92 (95% CI, 1.41–2.63), and for recent abacavir, cumulative lopinavir, indinavir, and darunavir exposure was OR = 1.82 (95% CI, 1.27–2.59), OR = 2.02 (95% CI, 1.34–3.04), OR = 3.42 (95% CI, 2.14–5.45), and OR = 1.66 (95% CI, 1.00–2.74), respectively. The TL-CAD association remained significant when adjusting only for Framingham risk score, when excluding TL outliers, and when adjusting for CMV-seropositivity, HCV-seropositivity, time spent with detectable HIV viremia, and injection drug use. Conclusions: In PLWH, TL measured >9 years before, is independently associated with CAD events after adjusting for multiple traditional and HIV-related factors. Abstract : In a case-control study done in the Swiss Human Immunodeficiency Virus (HIV) Cohort Study (333 cases, 745 controls), telomere length was independently associated with coronary artery disease events after adjusting for multiple traditional and HIV-related factors.